Answer:
w(0) = 1
Step-by-step explanation:
If w(0) is true, replace all x in the equation with 0 and then solve
w(0) = 5^2(0) + 1
w(0) = 25(0) + 1
w(0) = 0+1
w(0) = 1
Answer:
x = 5 and y = 1 or (5, 1)
Step-by-step explanation:
2x -3y=7
3x-2y=13
Multiply (1st) equation by 3 and (2nd) equation by 2
6x -9y=21
6x-4y=26
----------------subtract
-5y = - 5
y = 1
Substitute y = 1 into 2x -3y=7
2x -3(1)=7
2x - 3 = 7
2x = 10
x = 5
Answer
x = 5 and y = 1 or (5, 1)
Answer:
16
5
O
I think
Step-by-step explanation: